An Episode in the History of an Acoustic Mask: Philadelphia, 1908 - Palmié, Stephan (Archives de sciences sociales des religions, 2019)
In 1908, two black Cuban brothers, held a temple on Philadelphia's North Fairmount Avenue, which appears to have combined Edinsonian sound technology with elements from the ritual repertoire of the Abakuá male esoteric brotherhood. I suggest that the technologically enriched "echo" of the Leal brothers can be analysed heuristically as the locus of a remarkable convergence between phonic and auditory ideologies underlying the mediation of the divine in the Abakuá, and acoustic transmission technologies through time and space - particularly telephony and phonography - that had begun to reconfigure the Western auditory worlds by the second half of the 19th century.